HUBUNGAN PERILAKU, PENGETAHUAN DAN PERAN AYAH (FATHERING) DALAM PENGASUHAN ANAK TERHADAP KEJADIAN PNEUMONIA PADA BALITA DI DESA PEGADINGAN KEC. KRAMATWATU KAB. SERANG - Jumiati; Nur Avenzoar (Poltekkes 'Aisyiyah Banten, 2021)
Background Parenting is a process of interaction between parents and children. The role of a father in the family is usually more of the backbone of the family and the breadwinner of the family, while the mother plays an active role in caring for her children. In fact, the role of parents, especially here father, is very much needed for the development of a child. Coparenting refers to the way for parents to work together as a couple, negotiate in raising children and support each other. The role of father (fathering) is as important as the role of mother and has an influence in the development of early childhood. Pneumonia is still a public health problem in Indonesia, especially for toddlers. According to the source of the Directorate General of P2P of the Indonesian Ministry of Health in 2017, it was found that the number of pneumonia cases in toddlers was 57.84% or 503,738 toddlers from the target of finding 870,893 cases of pneumonia in children under five, while in Banten Province, the number of pneumonia cases in toddlers was 57.84% or 503,738. Toddlers from the target of finding cases of pneumonia in children under five were 870,893 people. Research in 2017 of 95 toddlers who experienced pneumonia as much as 48%. The purpose of this study was to determine the relationship between father's behavior, knowledge and the role of father (fathering) in childcare for the incidence of pneumonia in toddlers in Pegadingan Village, Kec. Kramatwatu Research Methods This type of research is an observational analytic study, with the research design used is a cross sectional approach. The sample of this study consisted of 84 fathers who have children under five. Data processing was done by means of editing, scoring, coding and tabulating using univariate and bivariate data analysis. Results More than half of 52.4% of children under five had pneumonia, 57.1% of fathers had less knowledge about pneumonia, 58.3% of fathers had sick behavior, 71.4% of fathers had less roles. There is a significant relationship between the behavior and role of the father with the incidence of pneumonia and there is no significant relationship between knowledge and the incidence of pneumonia in children under five in Pegadingan Village, Kec. Kramatwatu Kab. Attack of the Year 2020 Suggestion Health workers further increase the promotion of the importance of routine monthly check-ups for toddlers by involving the participation of a father